Transcriptional control of lipid metabolism by the MarR‐like regulator FamR and the global regulator GlxR in the lipophilic axilla isolate Corynebacterium jeikeium K411. Issue 2 (20th November 2012) - Barzantny, Helena; Guttmann, Sarah; Lässig, Charlotte; Brune, Iris; Tauch, Andreas
Summary Corynebacterial fatty acid metabolism has been associated with human body odour, and is therefore discussed as a potential target for the development of new deodorant additives. For this reason, the transcription levels of fad genes associated with lipid metabolism in the axilla isolate Corynebacterium jeikeium were analysed during growth on different lipid sources. The transcription of several fad genes was induced two‐ to ninefold in the presence of Tween 60, including the acyl‐CoA dehydrogenase gene fadE6. DNA affinity chromatography identified the MarR‐like protein FamR as candidate regulator of fadE6. DNA band shift assays and in vivo reporter gene fusions confirmed the direct interaction of FamR with the mapped fadE6 promoter region. Moreover, DNA affinity chromatography and DNA band shift assays detected the binding of GlxR to the promoter regions of fadE6 and famR, revealing a hierarchical control of fadE6 transcription by a feed‐forward loop. Binding of GlxR and FamR to additional fad gene regions was demonstrated in vitro by DNA band shift assays, resulting in the co‐regulation of fadA, fadD, fadE and fadH genes. These results shed first light on the hierarchical transcriptional control of lipid metabolism in C. jeikeium, a pathway associated with the development of human axillary odour.